Some Acetophenone Derivatives as Corrosion Inhibitors for Diesel Fuels - Farzaliyeva, Aynur; Maharramov, Abel; Mamedov, Ibrahim (Indonesian Journal of Chemical Research, 2024)
The corrosion inhibition activities 2.4-dimethylasetophenone semicarbazone (1), 2.4-dimethylacetophenone thiosemicarbazone (2), (E)-3-(2-allyloxy)phenyl)-1-(4-hydroxy-2-methylphenyl)prop-2-en-1-one (3), (E,E)-3-(5-bromo-2-hydroxyphenyl)-1-(4-hydroxy-2-methylphenyl)prop-2-en-1-one thiosemicarbazone (4) and 3-hydroxy-3-(2-(2-hydroxy-5-methylphenyl)-2-oxoethyl)indolin-2-one (5) have been studied by weight loss measurements for mild steel-3 specimen in diesel fuel. The corrosion rates of the steel-3 are decreased with the increase of the carbazones, chalcone, indolinone concentration, while the inhibition efficiencies are increased.